QUALITATIVE YIELD OF WHITE PEPPER EXTRACT OPTIMIZED BY MICROWAVE EXTRACTION AND MEAT QUALITY ASSESSMENT – AN ALTERNATIVE APPROACH - Adegoke, Adeola; Sanwo, Kehinde; Sobukola, Olajide; Egbeyale, Lawrence; Ekunseitan, Oluwakemi (Polish Journal of Natural Sciences, 2024)
This study experiments the application of closed microwave extraction on aqueous white pepper – guided by two fixed [microwave power (300W) and particle size (0.105 mm)] and two variable [irradiation time (75 – 85 min) and solvent volume (280 – 300 mL)] factors in a central composite design. Extracts generated were optimized via meat quality assessment. From responses generated post-optimization, twelve solutions were proffered. Five solutions had highest desirability value of 0.604. Extraction criteria for recommended desirability require microwave power of 300W, 0.105 mm particle size of white pepper, 91.19 min of irradiation time and 280 mL of solvent volume (distilled water), but the other four solutions all require 280 mL of solvent volume and 91.151, 91.131, 91.241 and 91.091 min of irradiation time respectively. Gas Chromatography Mass Spectrometry (GC-MS) analysis of the recommended extract had a remarkable yield of forty-one (41) compounds. This green extraction procedure shows promise for future extractions